Reducing hippocampal extracellular matrix reverses early memory deficits in a mouse model of Alzheimer’s disease - Végh, Marlene J (BioMed Central, 2014)
Alzheimer’s disease is caused by increased production or reduced clearance of amyloid-β, which results in the formation amyloid-β plaques and triggers a cascade of downstream events leading to progressive neurodegeneration. The earliest clinical symptoms of Alzheimer’s disease, i.e., memory loss, are however poorly understood from a molecular and cellular perspective. Here we used APPswe/PS1dE9 (APP/PS1) transgenic mice to study the early pre-pathological effects of increased amyloid-β levels on hippocampal synaptic plasticity and memory. Using an unbiased proteomics approach we show that the early increase in amyloid-β levels in APP/PS1 mice at three months of age coincides with a robust and significant upregulation of several protein components of the extracellular matrix in hippocampal synaptosome preparations. This increase in extracellular matrix levels occurred well before the onset of plaque formation and was paralleled by impairments in hippocampal long-term potentiation and contextual memory. Direct injection into the hippocampus of the extracellular matrix inactivating enzyme chondroitinase ABC restored both long-term potentiation and contextual memory performance. These findings indicate an important role for the extracellular matrix in causing early memory loss in Alzheimer’s disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40478-014-0076-z) contains supplementary material, which is available to authorized users.